Preparation and Characterization of Size-Controlled Lignin Nanoparticles with Deep Eutectic Solvents by Nanoprecipitation - Luo, Tong (Molecules, 2021)
Lignin nanomaterials have wide application prospects in the fields of cosmetics delivery, energy storage, and environmental governance. In this study, we developed a simple and sustainable synthesis approach to produce uniform lignin nanoparticles (LNPs) by dissolving industrial lignin in deep eutectic solvents (DESs) followed by a self-assembling process. LNPs with high yield could be obtained through nanoprecipitation. The LNPs were characterized by dynamic light scattering (DLS), transmission electron microscopy (TEM), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and gel permeation chromatography (GPC). Distinct LNPs could be produced by changing the type of DES, lignin sources, pre-dropping lignin concentration, and the pH of the system. Their diameter is in the range of 20–200 nm and they show excellent dispersibility and superior long-term stability. The method of preparing LNPs from lignin–DES with water as an anti-solvent is simple, rapid, and environmentally friendly. The outcome aids to further the advancement of lignin-based nanotechnology.